1993
DOI: 10.1007/bf01076773
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of vertebrate nonmuscle and smooth muscle myosin heavy chains and light chains

Abstract: In this article we review the various amino acids present in vertebrate nonmuscle and smooth muscle myosin that can undergo phosphorylation. The sites for phosphorylation in the 20 kD myosin light chain include serine-19 and threonine-18 which are substrates for myosin light chain kinase and serine-1 and/or -2 and threonine-9 which are substrates for protein kinase C. The sites in vertebrate smooth muscle and nonmuscle myosin heavy chains that can be phosphorylated by protein kinase C and casein kinase II are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(27 citation statements)
references
References 46 publications
0
27
0
Order By: Relevance
“…Equally important is the mechanism for the regulation of myosin II, which is known to involve phosphorylation of the regulatory light chain (MRLC) and possibly the heavy chain [12,13,14]. In vitro phosphorylation of MRLC at Thr18 and Ser19 stimulates the actin-activated ATPase of myosin II and filament assembly [15].…”
Section: Introductionmentioning
confidence: 99%
“…Equally important is the mechanism for the regulation of myosin II, which is known to involve phosphorylation of the regulatory light chain (MRLC) and possibly the heavy chain [12,13,14]. In vitro phosphorylation of MRLC at Thr18 and Ser19 stimulates the actin-activated ATPase of myosin II and filament assembly [15].…”
Section: Introductionmentioning
confidence: 99%
“…Platelet cytoskeletal reorganization, upon thrombin stimulation, is a highly dynamic process involving protein phosphorylation (9). Particularly, protein kinase C (PKC) phosphorylates non-muscle myosin heavy chain IIA (MHCIIA) at Ser-1917 of the C-terminal end in mast cells (10), and in platelets (11)(12)(13)(14)(15)(16). In platelets, at least four PKC isoforms (␣, ␤, ␦, ) are expressed (17,18), and it has become clear that each isoform plays a different role in platelet function, even including a negative role (19,20).…”
mentioning
confidence: 99%
“…Previous work showed that myosin II was activated by phosphorylation of its regulatory MLC at Ser19/Thr18, and the phosphorylation at MLC Ser19 was critical for actin assembly. 12,33 It was also reported to be involved in several cellular processes due to its motor on actin/myosin activation, such as cell contraction, cytokinesis, cell migration, and membrane blebbing. Thus, we hypothesized that the dynamic changes of actin might be related to MLC phosphorylation in mouse oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been known that activated myosin II enriched at the spindle poles could pull the actin filaments and generate a force to drive the spindle migration during oocyte meiosis. 11 In addition, Myosin II is activated by phosphorylation of its regulatory myosin light chain 2 (MLC2) which is crucial for the execution of cell division 12 . Previous study has shown that myosin light chain 2 (MLC2) is phosphorylated at Ser19, which allows myosin 2 to interact with actin, assemble an actomyosin complex and initiate contraction.…”
Section: Introductionmentioning
confidence: 99%